A high-viscosity acrylic adhesive for new energy vehicles

By cross-linking and polymerizing with cross-linked modified monomers and acrylic resin, a high-viscosity acrylic adhesive with a cross-linked network structure is solved, and the problem of limited high-temperature resistance in high-temperature environments is significantly improved.

CN119039908BActive Publication Date: 2025-03-18东莞市博翔电子材料有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411327109.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-18
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing new energy vehicle adhesives have limited high temperature resistance in high temperature environments, and the internal stress after curing is high, which can easily lead to pull-off of parts such as solder pads and affect the quality of the vehicle.

Method used

High-viscosity acrylic adhesive is made of raw materials including acrylic resin polymer, defoaming agent, anti-aging agent and reinforcement, and cross-linked and polymerized with other acrylic resin monomers through cross-linking and polymerization to form a cross-linked network structure.

Benefits of technology

It improves the adhesive bonding performance and high temperature resistance, enhances bonding strength, and maintains stable bonding performance under high temperature environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039908B_ABST
    Figure CN119039908B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of adhesives, and discloses a high-viscosity acrylic adhesive for new energy vehicles. The adhesive is formed by mixing an acrylic resin polymer as a main raw material with a defoamer, an antioxidant, etc., and a cross-linked network-like structure of an acrylic resin polymer can be obtained by preparing a cross-linked modified monomer containing multiple unsaturated olefinic substituents as one of the raw materials of the acrylic resin polymer. The cross-linked structure of the acrylic resin polymer has greater internal stress and can show more excellent bonding performance. The cross-linked modified monomer structure contains a large number of ether bonds generated by ring-opening addition reactions, and these ether bonds can generate hydrogen bonds with the adhered substrate, which can enhance the bonding performance of the adhesive. The increase in cross-linking density will cause the movement of the acrylic resin molecular chain itself to be hindered, and the rigid benzene ring structure and high bond energy silicon oxygen bond in the cross-linked modified monomer structure can synergistically improve the high temperature resistance of the adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a high-viscosity acrylic adhesive for new energy vehicles. Background Art

[0002] As the world pays more attention to environmental protection and sustainable development, new energy vehicles, as the future development direction of the automotive industry, are gradually occupying an important position in the market. With the rapid development of the new energy vehicle industry, the requirements for material performance are also increasing. Among them, adhesives, as one of the key materials for connection and sealing, play a vital role in the manufacturing process of new energy vehicles.

[0003] At present, the adhesives used in new energy vehicles mainly include epoxy adhesives and acrylic resin adhesives. Although epoxy adhesives have excellent bonding properties, the hardness of the glue after curing is too high, the internal stress is too large, and it is easy to pull off parts such as pads, so it has a negative impact on the quality of new energy vehicles. Acrylic adhesives can firmly bond a variety of materials, including metals, plastics, glass, etc., have good weather resistance and chemical corrosion resistance, and can maintain stable bonding performance in these harsh environments. Therefore, they have been widely used in the manufacture of new energy vehicles. However, new energy vehicles will face various complex environmental conditions such as high temperature during use, which requires acrylic resin adhesives to have good high temperature resistance and other properties, and need to maintain high viscosity. However, the heat resistance of acrylic resin adhesives is relatively limited, and there are also defects in practical applications. Therefore, it is of great significance to prepare acrylic resin adhesives with high viscosity and excellent high temperature resistance. Summary of the invention

[0004] 1. Technical issues to be resolved

[0005] In view of the deficiencies in the prior art, the present invention provides a high-viscosity acrylic adhesive for new energy vehicles.

[0006] (II) Technical solution

[0007] A high-viscosity acrylic adhesive for new energy vehicles is made from the following raw materials in parts by weight:

[0008] 36-42 parts of acrylic resin polymer;

[0009] 1-1.5 parts of defoaming agent;

[0010] 1-2 parts of antioxidant;

[0011] 3-6 servings of booster.

[0012] As a further embodiment of the present invention, the preparation method of the high-viscosity acrylic adhesive comprises the following steps:

[0013] The first step is to weigh all the raw materials according to the formula and set them aside;

[0014] The second step is to add the acrylic resin polymer, antioxidant and reinforcing agent into a high-speed mixer, and mechanically stir and mix them at a stirring rate of 1000-2000r / min for 10-30min, then adjust the stirring rate to 200-300r / min, and then add the defoaming agent. After stirring for 10-20min, stop stirring, let it stand for 1-2h, and discharge the material to obtain a high-viscosity acrylic adhesive.

[0015] As a further solution of the present invention, the preparation method of the acrylic resin polymer is as follows:

[0016] Methacrylic acid, methyl acrylate, isooctyl acrylate, glycidyl methacrylate and purified water are added to a reactor, nitrogen is introduced for protection, stirring is started, and after a uniform reaction liquid is formed, azobisisobutyronitrile is added to the reactor. After the addition is completed, the temperature is controlled at 78-83°C and kept warm for 1-2 hours. Then, the cross-linking modified monomer is added to the reactor. After the addition is completed, the temperature is kept warm for 8-12 hours, the heating is stopped, the nitrogen is removed, the temperature is lowered and the material is discharged to obtain an acrylic resin polymer.

[0017] As a further embodiment of the present invention, the mass ratio of methacrylic acid, methyl acrylate, isooctyl acrylate, glycidyl methacrylate, azobisisobutyronitrile and crosslinking modified monomer is 25-28:3-6:1-2:1-3:0.1-0.4:1-2.5.

[0018] As a further embodiment of the present invention, the preparation method of the cross-linking modified monomer is as follows:

[0019] Add 3-acryloyloxy-2-hydroxypropyl methacrylate, 1,5-bis(glycidoxypropyl)-3-phenyl-1,1,3,5,5-pentamethyltrisiloxane and N,N-dimethylformamide into a reaction kettle, start stirring until a uniform reaction liquid is formed, and then add a phase transfer catalyst to the reaction liquid. After the addition is completed, gradually increase the temperature to 60-70°C, keep warm for 2-4 hours under continuous stirring, remove the solvent by rotary evaporation, cool and discharge the material, and the cross-linked modified monomer can be obtained.

[0020] As a further embodiment of the present invention, the molar ratio of 3-acryloxy-2-hydroxypropyl methacrylate to 1,5-bis(glycidoxypropyl)-3-phenyl-1,1,3,5,5-pentamethyltrisiloxane is 1:1-2.

[0021] As a further embodiment of the present invention, the phase transfer catalyst is boron trifluoride ether complex.

[0022] In the above technical scheme, 3-acryloxy-2-hydroxypropyl methacrylate and 1,5-bis(glycidoxypropyl)-3-phenyl-1,1,3,5,5-pentamethyltrisiloxane are used as raw materials, and the principle that the active substituted hydroxyl groups and epoxy groups can undergo a ring-opening addition reaction under the catalysis of a phase transfer catalyst is utilized, and by controlling the dosage ratio of the two, a cross-linked modified monomer containing multiple active unsaturated olefinic substituents in the structure can be prepared.

[0023] As a further embodiment of the present invention, the defoaming agent is at least one of BYK-1790, BYK-061, BYK-052N, BYK-085 or BYK-065.

[0024] As a further embodiment of the present invention, the antioxidant is antioxidant 264 or antioxidant 4020.

[0025] As a further embodiment of the present invention, the reinforcing agent is at least one of polyether rubber, chloroether rubber, chloroprene rubber, nitrile rubber or styrene-butadiene rubber.

[0026] 3. Beneficial technical effects

[0027] The present invention prepares a cross-linked modified monomer containing multiple active unsaturated alkenyl substituents in the structure, and cross-links and polymerizes with other monomers of acrylic resin to obtain an acrylic resin polymer with a cross-linked network structure. First, the internal stress of the acrylic resin polymer with the cross-linked structure is greater, and it can show more excellent bonding performance, which has a good positive effect on improving the bonding strength of the adhesive. In addition, the cross-linked modified monomer structure contains a large number of ether bonds generated by the ring-opening addition reaction, and these ether bonds can generate hydrogen bonds with the adhered substrate, thereby further enhancing the bonding performance of the adhesive. In addition, the increase in cross-linking density will cause the movement of the acrylic resin's own molecular chain to be hindered, and the rigid benzene ring structure and high bond energy silicon oxygen bond in the cross-linked modified monomer structure can synergistically improve the high temperature resistance of the adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0029] Figure 1 This is the infrared analysis test diagram of the cross-linked modified monomer. DETAILED DESCRIPTION

[0030] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0031] Preparation Example 1

[0032] Preparation of acrylic resin polymer:

[0033] Step 1: add 0.2 g of 3-acryloyloxy-2-hydroxypropyl methacrylate, 0.9 g of 1,5-bis(glycidoxypropyl)-3-phenyl-1,1,3,5,5-pentamethyltrisiloxane and N,N-dimethylformamide to a reaction kettle, start stirring to form a uniform reaction solution, then add 0.01 g of boron trifluoride ether complex to the reaction solution, and after the addition, gradually increase the temperature to 65° C., keep warm for 3 hours under continuous stirring, remove the solvent by rotary evaporation, cool and discharge, and obtain a cross-linked modified monomer;

[0034] The infrared analysis test of the cross-linking modified monomer showed the following results: Figure 1 As shown, 3239cm -1 The absorption peak at 3094 cm is the characteristic absorption peak of hydroxyl group produced by the ring-opening reaction. -1 and 3072cm -1 The absorption peak at 3025cm is the characteristic absorption peak of carbon and hydrogen in the benzene ring skeleton. -1 The absorption peak at 1746 cm is the characteristic absorption peak of carbon-hydrogen double bond. -1 The absorption peak at 1000-1100 cm is the characteristic absorption peak of the carbon-oxygen double bond of the ester group. -1 The absorption peak that appears at is the characteristic absorption peak of the overlapping of ether bond and silicon oxygen bond.

[0035] Step 2: Add 2.6 g of methacrylic acid, 0.35 g of methyl acrylate, 0.2 g of isooctyl acrylate, 0.2 g of glycidyl methacrylate and 50 mL of purified water to a reactor, introduce nitrogen protection, start stirring, and after a uniform reaction liquid is formed, add 0.01 g of azobisisobutyronitrile to the reactor. After the addition is completed, control the temperature at 82 ° C. After keeping warm for 2 hours, add 0.15 g of a cross-linking modified monomer to the reactor. After the addition is completed, continue to keep warm for 9 hours, stop heating, remove nitrogen, cool and discharge, and obtain an acrylic resin polymer. Example

[0036] A high-viscosity acrylic adhesive for new energy vehicles is made from the following raw materials in parts by weight:

[0037] 36 parts of acrylic resin polymer;

[0038] Defoaming agent BYK-1790 1 part;

[0039] Anti-aging agent 264 1 part;

[0040] 3 parts of polyether rubber.

[0041] As a further embodiment of the present invention, the preparation method of the high-viscosity acrylic adhesive comprises the following steps:

[0042] The first step is to weigh all the raw materials according to the formula and set them aside;

[0043] In the second step, add the acrylic resin polymer, antioxidant 264 and polyether rubber into a high-speed mixer, stir and mix them mechanically at a stirring rate of 1000 r / min for 30 minutes, then adjust the stirring rate to 200 r / min, add the defoamer BYK-1790, stir for 10 minutes, stop stirring, let it stand for 2 hours, and discharge the material to obtain a high-viscosity acrylic adhesive.

[0044] The preparation method of the acrylic resin polymer is shown in Preparation Example 1, and the same is true for the following. Example

[0045] A high-viscosity acrylic adhesive for new energy vehicles is made from the following raw materials in parts by weight:

[0046] 40 parts of acrylic resin polymer;

[0047] Defoamer BYK-061 1.2 parts;

[0048] Antiaging agent 4020 1.5 parts;

[0049] 4 parts of chloroprene rubber.

[0050] As a further embodiment of the present invention, the preparation method of the high-viscosity acrylic adhesive comprises the following steps:

[0051] The first step is to weigh all the raw materials according to the formula and set them aside;

[0052] In the second step, add the acrylic resin polymer, antioxidant 4020 and chloroether rubber into the high-speed mixer, stir and mix them mechanically at a stirring rate of 1500r / min for 20 minutes, then adjust the stirring rate to 300r / min, add the defoamer BYK-061, stir for 15 minutes, stop stirring, let it stand for 1 hour, and discharge the material to obtain a high-viscosity acrylic adhesive. Example

[0053] A high-viscosity acrylic adhesive for new energy vehicles is made from the following raw materials in parts by weight:

[0054] 42 parts of acrylic resin polymer;

[0055] Defoamer BYK-085 1.5 parts;

[0056] Anti-aging agent 264 2 parts;

[0057] 6 parts of neoprene.

[0058] As a further embodiment of the present invention, the preparation method of the high-viscosity acrylic adhesive comprises the following steps:

[0059] The first step is to weigh all the raw materials according to the formula and set them aside;

[0060] In the second step, add the acrylic resin polymer, antioxidant and chloroprene rubber into the high-speed mixer, stir and mix them mechanically at a stirring rate of 2000r / min for 10 minutes, then adjust the stirring rate to 300r / min, add the defoamer BYK-085, stir for 10 minutes, stop stirring, let it stand for 2 hours, and discharge the material to obtain a high-viscosity acrylic adhesive.

[0061] Comparative Example 1

[0062] A high-viscosity acrylic adhesive for new energy vehicles is made from the following raw materials in parts by weight:

[0063] 40 parts of acrylic resin polymer;

[0064] Defoamer BYK-061 1.2 parts;

[0065] Antiaging agent 4020 1.5 parts;

[0066] 4 parts of chloroprene rubber.

[0067] As a further embodiment of the present invention, the preparation method of the high-viscosity acrylic adhesive comprises the following steps:

[0068] The first step is to weigh all the raw materials according to the formula and set them aside;

[0069] In the second step, add the acrylic resin polymer, antioxidant 4020 and chloroether rubber into the high-speed mixer, stir and mix them mechanically at a stirring rate of 1500r / min for 20 minutes, then adjust the stirring rate to 300r / min, add the defoamer BYK-061, stir for 15 minutes, stop stirring, let it stand for 1 hour, and discharge the material to obtain a high-viscosity acrylic adhesive.

[0070] The preparation method of the acrylic resin polymer is different from that of Preparation Example 1 in that no cross-linking modification monomer is added.

[0071] Test Case

[0072] With reference to the national standard GB / T 2791-1995, the adhesives in the embodiments and comparative examples were subjected to peel strength tests. After the tests were completed, the test samples of the same group were placed in an environment of 85°C and a relative humidity of 85% for 1 day, then taken out and subjected to peel strength tests again. The results are recorded in Table 1:

[0073] Table 1 - Test results

[0074]

[0075] Analysis of the test results in Table 1 shows that the acrylic resin adhesive prepared using a cross-linking modifier as a raw material has significantly better bonding performance, while the adhesive prepared without adding a cross-linking modifier as a raw material not only has a significantly reduced bonding performance, but also has poor high temperature resistance. This is because the acrylic resin polymer molecular chain prepared without adding a cross-linking modifier has a straight chain structure, is easily decomposed by heat, and does not contain rigid benzene rings, silicon oxygen bonds, and ether bond energy functional groups, so the overall performance is greatly reduced.

[0076] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.

Claims

1. An acrylic adhesive for new energy vehicles, characterized in that: Made of the following raw materials in parts by weight: 36-42 parts of acrylic resin polymer; Defoaming agent 1-1.5 parts; 1-2 parts of antioxidant; 3-6 parts of enhancer; The preparation method of the acrylic resin polymer is as follows: Add methacrylic acid, methyl acrylate, isooctyl acrylate, glycidyl methacrylate and purified water into a reactor, introduce nitrogen protection, start stirring, and after forming a uniform reaction liquid, add azobisisobutyronitrile to the reactor. After the addition is completed, control the temperature at 78-83°C and keep it warm for 1-2 hours. Then add the cross-linking modified monomer to the reactor. After the addition is completed, continue to keep it warm for 8-12 hours, stop heating, remove nitrogen, cool down and discharge the material to obtain an acrylic resin polymer; The mass ratio of methacrylic acid, methyl acrylate, isooctyl acrylate, glycidyl methacrylate, azobisisobutyronitrile and cross-linking modified monomer is 25-28: 3-6: 1-2: 1-3: 0.1-0.4: 1-2.5; The preparation method of the cross-linked modified monomer is as follows: Add 3-acryloyloxy-2-hydroxypropyl methacrylate, 1,5-bis(glycidoxypropyl)-3-phenyl-1,1,3,5,5-pentamethyltrisiloxane and N,N-dimethylformamide to the reaction kettle, start stirring until a uniform reaction liquid is formed, then add a phase transfer catalyst to the reaction liquid, after the addition is completed, gradually increase the temperature to 60-70°C, keep the temperature for 2-4 hours under continuous stirring, remove the solvent by rotary evaporation, cool and discharge the material, and the cross-linked modified monomer can be obtained; The molar ratio of 3-acryloyloxy-2-hydroxypropyl methacrylate and 1,5-bis(glycidoxypropyl)-3-phenyl-1,1,3,5,5-pentamethyltrisiloxane is 1:1-2; The phase transfer catalyst is boron trifluoride ether complex; The preparation method of the acrylic adhesive comprises the following steps: The first step is to weigh all the raw materials according to the formula and set them aside; The second step is to add the acrylic resin polymer, antioxidant and reinforcing agent into a high-speed mixer, and mechanically stir and mix them at a stirring rate of 1000-2000r / min for 10-30min, then adjust the stirring rate to 200-300r / min, and then add the defoaming agent. After stirring for 10-20min, stop stirring, let it stand for 1-2h, and discharge the material to obtain the acrylic adhesive.

2. The acrylic adhesive for new energy vehicles according to claim 1, characterized in that: The defoamer is at least one of BYK-1790, BYK-061, BYK-052N, BYK-085 or BYK-065.

3. The acrylic adhesive for new energy vehicles according to claim 1, characterized in that: The antioxidant is antioxidant 264 or antioxidant 4020.

4. The acrylic adhesive for new energy vehicles according to claim 1, characterized in that: The reinforcing agent is at least one of polyether rubber, chloroether rubber, chloroprene rubber, nitrile rubber or styrene-butadiene rubber.

Citation Information

Patent Citations

  • High-viscosity adhesive for protective film and preparation process of high-viscosity adhesive

    CN118638511A